Analisis dan Simulasi Distribusi Suhu Udara pada Kandang Sapi Perah Menggunakan Computational Fluid Dynamics (CFD) - A Yani; H Suhardiyanto; R Hasbullah; B P Purwanto (Media Peternakan, 2007)
This experiment was conducted to analyze the temperature and relative humidity distribution in dairy barn of Friesian Holstein (FH) using computational fluid dynamics (CFD) as a basic consideration for dairy barn design. The capacity of the dairy barn was 20 heads of FH with tail to tail model. The dimensions of the dairy barn were: 13 m in length, 6.3 m in width, and 5.75 m in height. The floor was made from concrete with 20 slope. Asbestos was used as roof of the dairy barn, whereas frame of the dairy barn was made from steel. The results of the analysis showed that during the daytime, air temperature inside the dairy barn increased by the height from floor level. The CFD simulation showed clearly the temperature distribution in the dairy barn. Air temperature obtained from CFD simulation was in line with that of the measured values. Therefore, it can be used as basic consideration for the dairy barn design with respect to low air temperature and uniform air temperature distribution. It was recommended that one of the best design configurations is 6.25 m high, 8.3 m wide, 0.4 m high of wall. The best design could decrease 0.474 0C of air temperature and increased dry matter intake of dairy cattle 0.403 kg per day per head. The amount of heat production of FH was considered to determine the best design of dairy barn. Key words: dairy barn design, air temperature distribution,computational fluid dynamics (CFD)